Uji Asosiasi Bakteri Rhizobium Terseleksi dengan Leguminosa Pakan dalam Kondisi Tercekam Salin - Eny Fuskhah; R. Djoko Soetrisno; Syaiful Anwar; Florentina Kusmiyati (Jurnal Agripet, 2014)
(Test of Association Selected Rhizobium Bacteria with Legumes in Salinity Stress) ABSTRACT. The research aim was to investigate association selected rhizobium bacteria with legumes in salinity stress. Plant media was salin soil that have EC = 20.45 mmhos/cm which taken from Morosari beach, Sayung, Demak. Rhizobium isolate applied was tolerant to 12.000 ppm of NaCl that equaled to electrical conductivity of 20 mmhos/cm. The research was carried out in green house of Laboratory of Forage Science Diponegoro University Semarang. The design arranged was completely randomized design with factorial design 2 x 4 in 3 repeatations. First factor was kind of legumes, T1 = lamtoro (Leucaena leucocephala); T2 = turi (Sesbania grandiflora). and second factor was kind of rhizobium isolates, I1 = without isolate; I2 = rhizobium that was isolated from lamtoro, I3 = rhizobium that was isolated from turi; I4 = combination isolate from lamtoro and turi. The crop growth was observed up to 10 weeks of age. The parameters were 1) crops heigh; 2) sum of leaf crops; 3) fresh weight production; 4) dry weight production; 5) amount and fresh weigh of effective root nodules. The study showed the growth and production of turi in saline media of EC 20.45 mmhos/cm was higher than lamtoro. Root nodule of turi was formed, but lamtoro was not. Turi was more tolerant than lamtoro at very saline media.